Study on anti-segregation performance of cement stabilized macadam and its impact on mechanical and shrinkage properties - Chen, Xiaokun; Deng, Caihong; Zhai, Xinming; Di, Wenjin; Cao, Xuanhao; Guan, Bowen (Frontiers in Materials, 2024)
This study systematically explores the relationship between the mechanical and shrinkage properties of cement-stabilized macadam (CSM) stone base layers and their resistance to segregation to address the issue of segregation in wide and thick base layers. It establishes three cement dosage levels and five aggregate gradation types (GW1, GW2, GW3, GW4, and GW5). This research evaluates the antisegregation performance of the mixtures by introducing the shape segregation coefficient L and the sieving segregation coefficient Seg and investigates how these properties influence segregation resistance. The findings revealed that mixtures with GW3 and GW4 gradations exhibit superior segregation resistance, with the most concentrated gradation curves in each zone. These mixtures form a robust force chain structure that resists segregation tendencies during descent. With a 5% cement content, the shape segregation coefficient L decreases by an average of 3.1%, and the sieve segregation coefficient Seg reduces by 14.0%. In addition, mixtures with GW3 and GW4 gradations show optimal drying shrinkage properties. Effective segregation-resistant gradations can significantly reduce the dry shrinkage coefficient of the specimens.